Yeast display biopanning identifies human antibodies targeting glioblastoma stem-like cells. Issue 1 (December 2017) - Zorniak, Michael; Clark, Paul; Umlauf, Benjamin; Cho, Yongku; Shusta, Eric; Kuo, John
Abstract Glioblastoma stem-like cells (GSC) are hypothesized to evade current therapies and cause tumor recurrence, contributing to poor patient survival. Existing cell surface markers for GSC are developed from embryonic or neural stem cell systems; however, currently available GSC markers are suboptimal in sensitivity and specificity. We hypothesized that the GSC cell surface proteome could be mined with a yeast display antibody library to reveal novel immunophenotypes. We isolated an extensive collection of antibodies that were differentially selective for GSC. A single domain antibody VH-9.7 showed selectivity for five distinct patient-derived GSC lines and visualized orthotopic GBM xenograftsin vivo after conjugation with a near-infrared dye. These findings demonstrate a previously unexplored high-throughput strategy for GSC-selective antibody discovery, to aid in GSC isolation, diagnostic imaging, and therapeutic targeting.